Avaliação do potencial de descoloração de corantes azo por sistemas biológicos anaeróbios-aeróbios - Barbosa, Plínio Tavares (2024)
Color removal remains one of the greatest challenges faced by wastewater treatment plants in the textile industry, and the discharge of colored effluents can cause serious environmental problems. However, the biological treatment of textile effluents has stood out for being less harmful to the environment and achieving good color removal efficiencies. This study evaluated the decolorization capacity of azo dyes using different anaerobic-aerobic biological systems. In the first study, the effects of different conditions were investigated, such as variation of the dye structure, type of substrate (acetate, glucose, propionate, and ethanol), presence of redox mediator, and presence of alternative electron acceptors. In the second and third studies, operational parameters were investigated, such as hydraulic detention time (HRT) of the reactors, dye concentration, and effluent recirculation, influence of the redox mediator as well as system configurations employing acidogenic reactors and aerobic granular sludge (AGS) reactors, moving bed biofilm reactors (MBBRs), and trickling filters (TFs) as post-treatment for textile effluents in the presence of redox mediator. Regarding substrates, the decolorization efficiencies of Reactive Black 5 (RB5) ranged from 75% to 83%, with propionate showing better performance. The addition of redox mediators mainly impacted the kinetics of the reaction, AQS showed better results in general, especially at 50 μM, when a kinetic constant was obtained 30% higher than that of the control and the assay with AQDS at 50 μM. The different structures of the dyes impacted the removal process, with Reative Red 120 presenting the worst result, with 14.4% without the addition of AQS and 25% with 50 μM of AQS. Reactive Orange 16 had high sensitivity to the presence of the mediator, with removal of 48% without AQS and 97.1% with 50 μM of the mediator. The presence of sulfate inhibited the reduction of RB5, obtaining removal of only 60%, but the addition of AQS increased the decolorization to 78.1%. In the presence of nitrate, removal decreased to 32.5%, an effect minimized with AQS supplementation, which improved the dye reduction to 47.6%. A continuous experiment was also carried out in two AGS reactors (one control and another supplemented with AQS) to evaluate the impact of the presence of the dye and the redox mediator on their performance and stability. The reactors showed high COD removal (> 90%). The settleability of the reactor with RB5 was unstable throughout the experiment, being, however, similar to the control reactor, indicating that the presence of RB5 and AQS were not responsible for this. As for nutrients, the removal of ammonia was ~98%, that of total nitrogen was 80%, while the removal of phosphorus was less than 30%. The average color removal efficiency, without AQS, was close to 65%, increasing to 80% with the addition of AQS. In the second study, two acidogenic systems connected in series with AGS reactors (one control and another supplemented with AQS) were used to remove the color of the azo dye RB5 (50 mg·L- 1 ). The highest dye removal averages were obtained with the HRT of 3 h, with approximately 68% and 45% in acidogenic reactors with and without AQS, respectively. During stage IV, with an HRT of 2 h in the acidogenic reactors, the total efficiencies were approximately 72% in the system with AQS and 68% for the control. The ratio of SVI30/SVI5 in AGS reactors was greater than 80% until stage III. COD and ammonia removals were not negatively impacted, with removals exceeding 90% in all stages. The reactors showed low performance in phosphorus removal, with values around 21% in both systems. In the third study, acidogenic reactors were used followed by aerobic reactors, namely MBBRs and TFs, to evaluate the color removal of the azo dye RB5 also at 50 mg·L-1. The effects of the HRT (6 and 4 h) in the MBBR, the type of support medium in the TFs (polyurethane foam cubes and K1 biomedia), as well as the effect of the redox mediator anthraquinone-2-sodium disulfonate (AQS) (50 μM) were evaluated for color removal. The addition of AQS significantly improved the decolorization efficiency, with the acidogenic reactors being responsible for 96% of the discoloration of the systems, whereas, in the acidogenic reactor without mediator, this efficiency was 84%. The use of a lower HRT (4 h) in the MBBR negatively influenced the color and COD removal performance in the reactors. Polyurethane foam proved to be more viable for use as a support medium, as it is a more accessible and low-cost material. Finally, the use of an acidogenic reactor followed by a TF filled with polyurethane foam proved to be the most promising design, both in terms of removing color, COD, and ammonia, and in relation to the energy demand for system aeration.